Investigation of mall atmosphere in experiential shopping during holiday season: A case of Malaysian Shopping Malls - Ong, Derek Lai Teik *; Gan, Yi Hao *; Juniaty, Iva *; Wong, Joseanne Lirn Jhet *; Ling, Ai Rick *; Subashini a/p Gullantheivello, * (Zia World Press, Australia, 2015)
This study examines the influence of environmental factors in a shopping mall on consumer behaviour especially during holiday season. Within a shopping mall there needs to be a balance of external environment elements that serves to elicit human stimuli to help induce different sensations and psychological effects on a person, ultimately leading to positive consumer behaviours and increased purchase intentions. However the wrong balance of these elements can hinder the positive reactions of consumers especially during the holiday season shopping where potentially sales are at the highest. This study employed a convenience sampling data collection method from 300 respondents in a selected shopping mall during the month of December 2013 to capture the consumer’s reaction to the mall’s atmosphere which were enhanced with festive decorations to help induce potential buying behaviour. Results were collated based on the analysis of four significant environmental variables which are interior settings, music, employee engagement and consumer density. The findings indicated that the effects of interior settings, music and employee engagement were found to be evident. Conversely, consumer density was found to elicit no effect on consumer behaviour. It was also noted that gender moderates the relationship between music and consumer behaviour. The implications of the results obtained are discussed along with the managerial implications, limitations and future research.